Age Related Histological Changes in the Epithelium of Bursa of Fabricius in Chabro Bird - Anand Singh; S.P. Singh; M.M. Farooqui; Archana Pathak (Indian Journal of Veterinary Anatomy, 2026)
The study aimed to provide basic findings about the age-related epithelial changes in the lymphoid follicle of bursa of Fabricius, which was conducted on the bursa of Fabricius of thirty Chabro birds. The birds were selected after hatching irrespective of sex and divided into five groups (0, 30, 60, 90 and 150 days of age) each group comprised of 6 birds. The bursa of Fabricius was a sac-like structure connected to the dorsal wall of the proctodeum of the cloaca by a small stalk. As the age increases, there was increase and decrease in the height and width of surface epithelium and formation of an epithelial cyst.